1998
DOI: 10.3176/chem.1998.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Exposure on the Uptake and Destruction of Hematoporphyrin Derivative in Ehrlich Carcinoma Cell Suspension

Abstract: A mixture of porphyrins derived from hematoporphyrin and termed hematoporphyrin derivative (HpD) has been used for localization and photodynamic therapy (PDT) of tumours. Our data showed that HpD photobleached more rapidly when incorporated into tumour cells than in simple aqueous solutions. At light doses that are usually used in PDT about 30-40% of the HpD added to the cell suspension can be destroyed. In addition to photochemical modification, which leaves the porphyrin ring intact, more "drastic" reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…5 min after the addition of a PS, the cells were irradiated at 665 or 630 nm for E 6 and HpD, respectively. Our prior studies [25,26] showed that after a short incubation time (5 min) approximately 20-25% of the initial content of HpD (1 ug ml™") or E 6 (2 uM) is bound to EAC cells. It was also found that the presence of non-bound PSs in a medium has a negligible effect on the rate of HpDor E6-photosensitized damage of the cells.…”
Section: Light Sourcementioning
confidence: 98%
“…5 min after the addition of a PS, the cells were irradiated at 665 or 630 nm for E 6 and HpD, respectively. Our prior studies [25,26] showed that after a short incubation time (5 min) approximately 20-25% of the initial content of HpD (1 ug ml™") or E 6 (2 uM) is bound to EAC cells. It was also found that the presence of non-bound PSs in a medium has a negligible effect on the rate of HpDor E6-photosensitized damage of the cells.…”
Section: Light Sourcementioning
confidence: 98%